Techniques Enabling Language Models to Solve Competition-Level Software Engineering Problems - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 4 peer-reviewed papers addressing the following research question: What techniques enable language models to solve competition-level software engineering problems v12. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.0/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.